PENINGKATAN KECERDASAN INTRAPERSONAL DAN KECERDASAN INTERPERSONAL MELALUI PEMBELAJARAN PROJECT APPROACH - Ade Dwi Utami (Jurnal Ilmiah Visi, 2012)
The purpose of this research is to obtain empirical information on improving intrapersonal intelligence and interpersonal intelligence with project approach instruction particularly for Kindergarten children of B group. The research was conducted at Taman Tumbuh Kembang Anak Ceria, Universitas Negeri Jakarta, Jakarta, as from November 2008 through February 2009, employing action research method in two cycles. After comparing and analyzing the results of cycles I and II, the research concluded there is significant improvement of intrapersonal intelligence and interpersonal intelligence with project approach instruction, achieved by the kindergarten children in TTKA Ceria.